Long-term left ventricular assist device support reinforces detrimental immunological effects - Dieterlen, Maja-Theresa; Sauskat, Malina; Klaeske, Kristin; Messer, Eva Katharina; Jozwiak-Nozdrzykowska, Joanna; Dashkevich, Alexey; Borger, Michael A.; Eifert, Sandra; Nozdrzykowski, Michal (Frontiers in Immunology, 2026)
IntroductionInfection is a common complication following left ventricular assist device (LVAD) implantation that increases the mortality in the post-implantation period. Immunological changes affecting dendritic cells (DCs), natural killer (NK) cells and T-cells have been observed in the first year after implantation, but long-term data are missing. We investigated if long-term LVAD support has stronger effects on the immune system than short-term LVAD support.MethodsBlood samples were obtained from patients with 12–18 months of LVAD support (short-term LVAD; n=53) and from patients with ≥36 months of LVAD support (long-term LVAD; n=57). Flow cytometric analyses for CD4+ and CD8+ T-cells, Tregs, B cells, NK cells and DCs were performed. Additionally, terminal differentiation and activation of immune cells was quantified.ResultsBoth groups were comparable with regard to sex, age at LVAD implantation, preoperative BMI, etiology of heart failure, NYHA class, left ventricular ejection fraction, INTERMACS, and implant strategy. Platelet counts were lower in the long-term LVAD group (p=0.05). Flow cytometric analyses for CD4+ and CD8+ T-cells, Tregs, B-cells, NK cells and DCs revealed that the percentages of total DCs (p<0,01), BDCA3+ myeloid DCs (p<0.01), BDCA2+ (p=0.01) and BDCA4+ plasmacytoid DCs (p=0.02), CD19+ B-cells (p<0.01) and of immunoregulatory CD56bright NK cells (p<0.01) were reduced in long-term compared to short-term LVAD patients. Terminal differentiation of NK cells measured by CD57 expression was higher in long-term than in short-term LVAD patients (p=0.03).ConclusionThis cross-sectional observational study revealed that long-term (≥36 months) LVAD support may contribute to detrimental effects on the immune system in comparison to short-term LVAD support. The long-lasting LVAD support may influence DCs, NK cells and B-cells that show a progression of cellular changes.